36x-4x+9+25x+7=

Simple and best practice solution for 36x-4x+9+25x+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36x-4x+9+25x+7= equation:


Simplifying
36x + -4x + 9 + 25x + 7 = 0

Reorder the terms:
9 + 7 + 36x + -4x + 25x = 0

Combine like terms: 9 + 7 = 16
16 + 36x + -4x + 25x = 0

Combine like terms: 36x + -4x = 32x
16 + 32x + 25x = 0

Combine like terms: 32x + 25x = 57x
16 + 57x = 0

Solving
16 + 57x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 57x = 0 + -16

Combine like terms: 16 + -16 = 0
0 + 57x = 0 + -16
57x = 0 + -16

Combine like terms: 0 + -16 = -16
57x = -16

Divide each side by '57'.
x = -0.2807017544

Simplifying
x = -0.2807017544

See similar equations:

| (3x^2-6)=0 | | -(6(5xy+y^3)+5(9xy+7y^3))= | | -2a-11=7+7a | | 5x+5=-21-7x | | -3x^2-4x-5=0 | | 12p+6q=114 | | 2x*2x*2x+3x*3x*3x= | | 6a+2b=20 | | 160x-.8x^2=0 | | 200.00m+(-5600.00)=-2800.00 | | -5(x+5)=-15 | | 6p+4q=56 | | 3+2x=2(2+2x) | | 6x+-9=33 | | 200.00m+(-5600.00)=0.00 | | 3x-2(x+4)=15 | | -1.25+0.15m=0 | | (4,-4)=-5/8 | | (11w+13)+(4w-28)=180 | | 3x+7t=5 | | 3p+4q=44 | | 2x+40=16+5x | | 7-8x=202-43x | | 9x-3=-1 | | 5+2x=3x | | 2(z-3)-x=-1 | | 13x^2-30=28 | | 5+2(x+5)=45 | | -30+8x=4x+34 | | 0.3t=0.4+0.1t | | X-2=7x+2 | | 4x+80=-90-10x |

Equations solver categories